Hypertension, diabetes, and cardiovascular disease nexus: investigating the role of urbanization and lifestyle in Cabo Verde - Aaron Kobina Christian; Akosua Afriyie Osei-Appaw; Ruth Tobi Sawyerr; Martin Wiredu Agyekum (Global Health Action)
Background Although hypertension and diabetes are known to increase cardiovascular disease risk, the influencing and underlying factors remain unclear. Objective To examine the mediating effect of location of residence and the moderating effects of recommended lifestyle practices in the hypertension/diabetes and cardiovascular disease nexus. Material and methods Data were drawn from 4,563 participants in Steps 1 and 2 of the 2020 World Health Organization’s STEPS survey in Cabo Verde, with a subsample of 2,436 individuals completing Step 3. A logit regression model was employed to examine the correlations of cardiovascular disease, while structural equation modeling and interaction analysis were used to identify mediators and moderators within the explored relationships. Results Living with hypertension and diabetes were both observed to increase the likelihood of having a cardiovascular disease [Coeff. (RSE), 0.46, (0.12), p < 0.001; 1.26, (0.14), p < 0.001, respectively]. We identify urbanicity as a potential mediator through which hypertension/diabetes leads to a cardiovascular disease and waist circumference as a moderator of hypertension/diabetes-cardiovascular nexus. Conclusion These findings add to the toolset of public health practitioners and policymakers in formulating policies and interventions aimed at managing cardiovascular diseases, particularly in developing nations.